2016
DOI: 10.21037/jss.2016.12.04
|View full text |Cite
|
Sign up to set email alerts
|

Three-year follow-up of a randomized controlled trial comparing preoperative neuroscience education for patients undergoing surgery for lumbar radiculopathy

Abstract: Adding a single PNE session prior to surgery for lumbar radiculopathy results in significant healthcare savings over 3 years. Educating such patients about normal responses to lumbar surgery (LS) in a neuroscience framework may result in lasting behavior changes following surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 52 publications
0
50
0
9
Order By: Relevance
“…Louw et al [11] evaluated an intervention with neuroscience education compared to a control-group. The intervention-group reported that they were better prepared, that surgery had met their expectations to a higher extend, and they utilised less health care, both at the 1-year [11] and 3-year follow-up [35].…”
Section: Discussionmentioning
confidence: 99%
“…Louw et al [11] evaluated an intervention with neuroscience education compared to a control-group. The intervention-group reported that they were better prepared, that surgery had met their expectations to a higher extend, and they utilised less health care, both at the 1-year [11] and 3-year follow-up [35].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the effect was related to a change in behaviour towards more self-management (66). This effect was sustained at the 3-year follow-up (66,70). The work reported here does not include analyses of healthcare use nor recurrence rate, but the 2-year follow-up will reveal whether the higher activity level is associated with fewer recurrences.…”
Section: Pre-surgery Physiotherapy -Patient-reported Outcome Measuresmentioning
confidence: 88%
“…The mean age of the participants was 50 years, and they had experienced pain for less than 90 days. The pain education did not improve function, nor reduce back or leg pain compared to the control group, but gave long-term effects: healthcare consumption 1 year and 3 years post-surgery was lower (66,70). The pain education was developed by Butler and Moseley and is well-known as "Explain Pain".…”
Section: Pain Biology Education With a Cognitive Behavioural Approachmentioning
confidence: 99%
See 2 more Smart Citations